Conditional Knockout of the MicroRNA 17-92 Cluster in Type-I Collagen-Expressing Cells Decreases Alveolar Bone Size and Incisor Tooth Mechanical Properties - Ibrahim, M; Mohan, S; Xing, M J; Kesavan, C (Folia biologica, 2016)
To test the role of the miR17-92 (miR) cluster in dental bones, we evaluated the incisor tooth phenotype by micro-CT in 5- and 12-week-old conditional knockout (CKO) mice deficient in the miR17-92 cluster in type-I collagen-expressing cells and bone strength by finite element analysis. The incisor teeth of CKO mice showed a 23-30 % reduction in tissue volume and bone volume. Accordingly, the stiffness and failure load of incisor teeth assessed by finite element analysis showed an 18-40 % decrease in CKO compared to wild-type mice. A positive correlation between bone parameters and strength data suggests that the decreased mechanical properties of incisor teeth are due to decreased tissue volume and bone volume. Subsequently, we found that the width of alveolar bone was reduced by 25 % with a 16 % increase in periodontal ligament space, suggesting that the CKO mice are more susceptible to tooth movement. Since alveolar bone is populated primarily by osteoblast lineage cells, it is likely that the reduction in periosteal expansion of alveolar bone in the lower jaw of CKO mice results from decreased periosteal bone formation. Overall, our phenotype analysis demonstrates that the miR17-92 cluster is essential for development and maintenance of tooth strength by regulating its tooth size.
Keywords: Animals; kolagen typu I; Base Sequence; Mice, Knockout; Organ Size; myši knockoutované; rentgenová mikrotomografie; biomechanika; velikost orgánu; Incisor; mikro RNA; processus alveolaris; sekvence nukleotidů; řezáky; MicroRNAs; Alveolar Process; zvířata; Collagen Type I; X-Ray Microtomography; Biomechanical Phenomena